A Restitution Model of Two-car Collinear Collisions - Batista, Milan; Zovak, Goran (Promet - Traffic&Transportation, 2007)
In the paper two-car collinear collisions are discussed usingNewton's law of mechanics, conservation of energy and linearconstitutive law connecting impact force and crush. Two waysof calculating the mutual restitution coefficient are given: onebased on car masses and one based on car stiffness. A numericalexample of an actual test is provided.